Pengaruh Pembiayaan dan Nisbah Bagi Hasil terhadap Pendapatan para Anggota Koperasi - Noviardi, Ikhwan; Setiawani, Paramitha (Lembaga Yasin AlSys, 2022)
Cooperative financing with a profit-sharing system that is not burdensome on one side has a role and contribution in increasing income, but the problem faced is that the success in increasing income has not been effective. . The formulation of the problem in this study is whether financing affects the income of cooperative members and whether profit sharing ratios affect the income of cooperative members and whether financing and profit sharing ratios simultaneously affect the income of cooperative members at KSU Baitul Qiradh An-Nahl Central Aceh District . This study aims to explain the Effect of Financing and Profit Sharing Ratios on the Income of Cooperative Members (Studies at KSU Baitul Qiradh An-Nahl, Central Aceh District). This research is categorized in quantitative research with an associative approach. The population in this study amounted to 33 respondents with a sampling technique using saturated sampling, that is, all populations were used as samples. Sources of data in this study are primary data and secondary data with research instruments in the form of questionnaires and documentation. The data analysis technique used is multiple linear regression test. The results of the research based on the t test show that partially the financing variable has a positive and significant effect on income and for the profit sharing ratio variable it shows that the profit sharing ratio has a positive and significant effect on income. Meanwhile, based on the results of the f test, it shows that financing and profit sharing ratios have a positive and significant simultaneous effect on the income of cooperative members at KSU Baitul Qiradh An-Nahl, Central Aceh District.